Adipose tissue in health and disease – implications to cardiovascular diseases - Rastas, Kaisa (My University, 2020)
Two major roles of adipose tissue are to function as a fat storage and an endocrine organ. Adipose tissue stores excess fat in adipocytes and releases when needed. Adipose tissue also secretes hormones, called adipokines, and cytokines, and so the tissue affects on whole body health. If adipose tissue becomes dysfunctional, for example due to adipocyte hypertrophy, adipokine secretion changes and may lead to low-grade inflammation, changes in insulin sensitivity of adipose tissue and disturbances in lipid metabolism. In time these changes have effects on whole body health, especially in cardiovascular system. Function of white adipose tissue depends partly on localisation of tissue. White adipose tissue types can be roughly divided to subcutaneous and visceral adipose tissue. These adipose tissue subtypes have slightly different gene and protein expression levels. Due to differences in function, subcutaneous and visceral adipose tissue effect on whole body metabolic and diseases varies. Visceral adipose tissue has traditionally considered metabolically more harmful. Since one main role of adipose tissue is to store fat, mechanisms regulating the transport of lipids to adipocytes is scientifically interesting. Cells have many systems for transporting fat molecules trough membranes, and fatty acid transport proteins, known as FATPs, are one of them. The FATP-family consists of six transmembrane proteins (FATP1-6), which vary from function, and their expression is tissue specific. The goal of the research was to investigate if the expression of FATP-proteins varies between subcutaneous and mediastinal (part of visceral fat) adipose tissue. Used methods were real-time-PCR (RT-PCR), Western blotting and immunohistochemistry. Differences in gene expression levels were measured by RT-PCR for each six members of FATP-family. RNA used for this experiment was isolated from human adipose tissue. All but FATP5 showed expression in adipose tissue, but only FATP2 and FATP6 had difference in gene expression. Next steps were proceeded only with FATP2. Western blot was done to see if protein expression correlates with gene expression. Proteins were isolated from human subcutaneous and mediastinal adipose tissue. Results were unclear and could not confirm RT-PCR results. Location of FATP2 in adipose tissue was also tried to detect by RT-PCR and immunohistochemistry. In RT-PCR adipose tissue was separated to adipocyte and stroma-vascular cellular fractions. FATP2 expression was higher in adipocytes and immunohistochemistry also confirmed this. In immunohistochemistry also vascular walls stained with FATP2-antibody. The research shows that FATPs (excluding FATP5) are expressed in adipose tissue, and FATP2 and FATP6 gene expressions are higher in mediastinal than in subcutaneous adipose tissue. Key words: adipose tissue, adipocyte, subcutaneous fat, visceral fat, fatty acid transport protein, FATP